MINDNOTES: A Mobile Platform to enable users to break stigma around mental health and connect with therapists - Chanda, Prateek; Wagh, Amogh; Johnson, Jemimah A; Renghe, Swaraj; D C, Vageesh; Mathews, George; Behar, Sapna; Bhola, Poornima; Rao, Girish; Sudhir, Paulomi; Srikanth, T K; Sharma, Amit; et al. (2021)
Abstract coming soon...